Changes in safety climate and teamwork in the operating room after implementation of a revised WHO checklist: a prospective interventional study. Issue 1 (December 2017) - Erestam, Sofia; Haglind, Eva; Bock, David; Andersson, Annette; Angenete, Eva
Abstract Background Inter-professional teamwork in the operating room is important for patient safety. The World Health Organization (WHO) checklist was introduced to improve intraoperative teamwork. The aim of this study was to evaluate the safety climate in a Swedish operating room setting before and after an intervention, using a revised version of the WHO checklist to improve teamwork. Methods This study is a single center prospective interventional study. Participants were personnel working in operating room teams including surgeons, anesthesiologists, scrub nurses, nurse anaesthetists and nurse assistants. The study started with pre-interventional observations of the WHO checklist use followed by education on safety climate, the WHO checklist, and non-technical skills in the operating room. Thereafter a revised version of the WHO checklist was introduced. Post-interventional observations regarding the performance of the WHO checklist were carried out. The Safety Attitude Questionnaire was used to assess safety climate at baseline and post-intervention. Results At baseline we discovered a need for improved teamwork and communication. The participants considered teamwork to be important for patient safety, but had different perceptions of good teamwork between professions. The intervention, a revised version of the WHO checklist, did not affect teamwork climate. Adherence to the revision of the checklist was insufficient, dominated by a lack of structure. Conclusions There was no significant change in teamwork climate by use of the revised WHO checklist, which may be due to insufficient implementation, as a lack of adherence to the WHO checklist was detected. We found deficiencies in teamwork and communication. Further studies exploring how to improve safety climate are needed. Trial registration NCT02329691 .